Sven Estridsen’s Incest and Divorce - Lund, Niels (Viking and Medieval Scandinavia, 2017)
Abstract It is rather baffling that Archbishop Adalbert of Hamburg-Bremen should have wanted to alienate Sven Estridsen, on whose cooperation he depended entirely for the pursuance of his mission in Denmark, by forcing the king to divorce his queen on grounds of consanguinity. The story is known exclusively from Adam of Bremen and forms part of the story he made up about Sven Forkbeard and all the hardships he had to suffer for his patricide and apostacy. The story breaks down on many chronological facts, such as the age of Olof Skötkonung at the death of his father. This implies that we can no longer regard the Polish princess who married Sven Forkbeard and Sigrid the Haughty as the same person in two different traditions. Whether Adam concocted this story to depict Adalbert as an uncompromising champion of faith and morals in his diocese or for other reasons is hard to tell.